New Synthetic Routes towards Soluble and Dissymmetric Triphenodioxazine Dyes Designed for Dye-Sensitized Solar Cells - Nicolas, Yohann; Allama, Fouzia; Lepeltier, Marc; Massin, Julien; Castet, Frédéric; Ducasse, Laurent; Hirsch, Lionel; Boubegtiten, Zahia; Jonusauskas, Gediminas; Olivier, Céline; Toupance, Thierry (Chemistry : a European journal, 2014)
New π‐conjugated structures are constantly the subject of research in dyes and pigments industry and electronic organic field. In this context, the triphenodioxazine (TPDO) core has often been used as efficient photostable pigments and once integrated in air stable n‐type organic field‐effect transistor (OFET). However, little attention has been paid to the TPDO core as soluble materials for optoelectronic devices, possibly due to the harsh synthetic conditions and the insolubility of many compounds. To benefit from the photostability of TPDO in dye‐sensitized solar cells (DSCs), an original synthetic pathway has been established to provide soluble and dissymmetric molecules applied to a suitable design for the sensitizers of DSC. The study has been pursued by the theoretical modeling of opto‐electronic properties, the optical and electronic characterizations of dyes and elaboration of efficient devices. The discovery of new synthetic pathways opens the way to innovative designs of TPDO for materials used in organic electronics. Push–pull dyes: New unsymmetrical push–pull triphenodioxazine dyes have been synthesized under mild conditions with fine control of isomerism showing high photostability (see figure). The dye‐sensitized solar cells, elaborated from TiO2, dyes, and the iodine/iodide redox couple reached a photoconversion yield of up to 6.3 %.